Young-Onset Breast Carcinoma Tends to Show a Higher Proportion of Triple-Negative Subtype: A Comparative Molecular and Pathological Analysis - Dewi, Citra; Sari, Nova; Sandria (Biomedical Journal of Indonesia, 2026)
Introduction. Breast carcinoma in young women is often associated with more aggressive molecular profiles and suboptimal therapeutic responses. This study was designed to compare the molecular and histopathological characteristics of patients younger than 40 years with those aged 40 years and above. Methods. This study employed a retrospective descriptive-analytic design using clinical and pathological data from 36 patients diagnosed with invasive breast carcinoma. All cases were collected from the Department of Anatomical Pathology at Mohammad Hoesin General Hospital in Palembang, Indonesia, in 2023. Results. The molecular subtype profile was similarly distributed across the two age categories, with no statistically significant difference by age (p = 0.789). However, the younger cohort showed a relatively higher proportion of triple-negative cases. Luminal B remained the most prevalent molecular subtype in both groups. Likewise, ER, PR, and HER2 expression showed no significant differences according to age (p > 0.05). All patients exhibited high Ki-67 expression, and grade III was the predominant histological grade in both groups. Dominant TILs were observed in only a small fraction of cases, with no statistically significant age-related difference. Conclusion. Although younger patients showed a relative proportion of triple-negative cases and all tumors demonstrated high proliferative activity, no statistically significant differences in molecular subtype distribution or other clinicopathological parameters were identified between the two age groups. Luminal B remained the predominant molecular subtype in both groups. These findings suggest that age-related biological differences may exist, but larger studies are needed to clarify this association.